Sex Differences in Physiological Stress Induced by a Long-Lasting Adventure Race: A Prospective Observational Analytical Study - Silva, Romeu P.M.; Vilaça, Alexandre; Guerra, Fredy D.; Mundim, Antonio V.; De Agostini, Guilherme G.; De Abreu, Luiz Carlos; Zhiguo, Zhang; Sorpreso, Isabel C.; Valenti, Vitor E. [UNESP]; Penha-Silva, Nilson (Thieme, 2020)
Background In order to provide additional information on the behaviour of biochemical parameters related to stress responses to a specific long-term competition, we aimed to compare the stressful effects of a long-lasting competition on physiological variables in men and women. Methods This is a prospective observational analytical study. Twenty-five professional athletes, 15 men and 10 women, travelled 460 km for 4 days in an international edition of the Ecomotion/Pro AR World. Results After the competition, we detected an increase in α-amylase and cortisol levels and a decrease in salivary immunoglobulin A (lgA) levels. The relative percentage changes in α-amylase, IgA and cortisol levels were significantly higher in women than in men, whereas women had lower relative percentage changes in glucose and lactate levels compared with men. There was a decrease in lymphocyte, eosinophil and monocyte counts, with relative percentage decreases in lymphocytes and monocytes being significantly higher in female athletes than in males. There were increases in the serum activities of total creatine kinase (CK), the creatine kinase myocardial isoform (CKMB), alanine aminotransferase (ALT), aspartate aminotransferase (AST) and lactate dehydrogenase (LDH) at the end of the test, with significantly higher elevations of total CK, CKMB and LDH in men and ALT in women. Conclusion Long-lasting competition induced stress, muscle damage, anaemia and changes in the immune system. Women had more intense responses of cortisol and leukocytes.
Keywords: blood cells; blood chemical analysis; exercise; haematocrit; hydrocortisone; stress, physiological